2021
DOI: 10.1128/mbio.03456-20
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Genomic Variation in Space and Time in Hospitalized Patients in Philadelphia

Abstract: The severe acute respiratory coronavirus 2 (SARS-CoV-2) is the cause of the global outbreak of COVID-19. The epidemic accelerated in Philadelphia, PA, in the spring of 2020, with the city experiencing a first peak of infections on 15 April, followed by a decline through midsummer. Here, we investigate spread of the epidemic in the first wave in Philadelphia using full-genome sequencing of 52 SARS-CoV-2 samples obtained from 27 hospitalized patients collected between 30 March and 17 July 2020. Sequences most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…There was no association between SARS-CoV-2 RNA levels and WHO score or clinical outcomes (Wilcoxon rank sum test). Complete SARS-CoV-2 genome sequences were determined for 26 subjects as recently reported ( 20 ). All viral genomes were members of the B.1 lineage, which encodes the D614G variant in spike, and most also had the P314L variant in the RNA-dependent RNA polymerase (RdRp) located on ORF1b ( 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no association between SARS-CoV-2 RNA levels and WHO score or clinical outcomes (Wilcoxon rank sum test). Complete SARS-CoV-2 genome sequences were determined for 26 subjects as recently reported ( 20 ). All viral genomes were members of the B.1 lineage, which encodes the D614G variant in spike, and most also had the P314L variant in the RNA-dependent RNA polymerase (RdRp) located on ORF1b ( 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Oropharyngeal (OP) and nasopharyngeal (NP) swabs, and endotracheal aspirates (ETA) from intubated subjects, were obtained as previously described ( 18 ). Additional OP and NP swabs were obtained and eluted in viral transport medium (VTM) for SARS-CoV-2 analysis as previously described ( 20 ). COVID-19 patients were classified clinically by maximum score reached during hospitalization using the 11-point WHO COVID-19 progression scale ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…The first three cases (20–1891820–1930320–19305) are classified as "S" type for the Chilean strains. Meanwhile, the fourth case (20–19731) is a "G" type, according to nucleotide substitutions in the positions 28 144 and 23 403 11 Everett [ 30 ] Research article USA COIVD-19 patients D614G, RNA-dependent RNA polymerase (RdRp) located on ORF1b The D614G substitution has been proposed to promote infection of human cells, and this variant has spread globally at the expense of other genotypes 12 Forni [ 31 ] Original article Italy SARS-CoV-2 genomes D614G Recent studies have indicated that the D614G variant, which is now prevalent worldwide, enhances viral infectivity 13 Forster [ 32 ] Research article Germany COVID-19 patients Three central variants: A variant B variant C variant Node B is derived from A by two mutations: the synonymous mutation T8782C and the non-synonymous mutation C28144T changing a leucine to a serine. Type C differs from its parent type B by the non-synonymous mutation G26144T, which changes a glycine to a valine 14 Gómez-Carballa [ 33 ] Research article Spain SARS-CoV-2 genomes C8782T, C18060T, T28144C, C29095T Sub-haplogroup A2 most likely originated in Europe from an Asian ancestor and gave rise to sub-clade A2a, which represents the major non-Asian outbreak, especially in Africa and Europe 15 Goren [ 34 ] Letter to the editor USA COIVD-19 patients TMPRSS2 Both SARS-CoV-2 and influenza are dependent on TMPRSS2 for infectivity, it is likely that SARS-CoV-2 will have a similar seasonal cycle; thus, the fall and winter are likely to see an increase in COVID-19 cases 16 Graudenzi [ 35 ] Research ...…”
Section: Resultsmentioning
confidence: 99%
“…Of the 63 publications included, five were non-peer reviewed preprints [16,17,52,54,66]. Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73]. The remaining 33 articles analyzed SARS-CoV-2 genomes downloaded from the GISAID or other available databases with patient status [8][9][10][11]20,21,[30][31][32][33][34][35][36]40,50,…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
“…A total of 45 articles addressed the effect of viral mutations on severity of COVID-19 in patients, of which fifteen studies (five bigdata analyses [21,30,33,34,40] and ten clinical studies [39,[41][42][43][44][45][46][47][48][49]) showed no association between SARS-CoV-2 variants and severity of disease. Three studies (one bigdata analysis [50] and two clinical studies [17,51]) reported that the SARS-CoV-2 variants were significantly associated with decrease in severity of disease.…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 99%